Pengaruh Review Produk Dan Rating Toko Terhadap Minat Beli Pengguna Shopee Di Kota Tanjungpinang Melalui Kepercayaan Konsumen Sebagai Variabel Intervening - Yasih Williansari, Yash Williansari; Yusrizal; Putri Dewi, Selvia; Husna, Asmaul (Program Studi Manajemen FEBM UMRAH, 2025)
This study aims to analyze the influence of product reviews and store ratings on the purchase intention of Shopee users in Tanjungpinang City through costumer trust as an intervening variable. This study is a quantitative study using primary data with a population of Shopee users in Tanjungpinang City. The sampling technique used non-probability sampling with a purposive sampling selection method, the number of respondents was 100 respondents. Data collection was carried out through an online questionnaire using a 5-point Likert scale. The data analysis technique in this study used path analysis using SmartPLS 4.0 software. The results of this study indicate that product reviews and store ratings have a significant effect on the purchase intention of Shopee users in Tanjungpinang City through costumer trust as an intervening variable